Multiplicative Isometries on Classes Mp(X) of Holomorphic Functions - Yasuo Iida; Kazuhiro Kasuga (Journal of Function Spaces)
In (Iida and Kasuga 2013), the authors described multiplicative (but not necessarily linear) isometries of Mp(X) onto Mp(X) in the case of positive integer p∈N, where Mp(X)  (p≥1) is included in the Smirnov class N∗(X). In this paper, we will generalize the result to arbitrary (not necessarily positive integer) value of the exponents 0<p<∞.